Giant topological longitudinal circular photo-galvanic effect in the chiral multifold semimetal CoSi - Zhuoliang Ni (Nature Portfolio, 2021)
Quantized circular photogalvanic effect (CPGE) is predicted in chiral topological semimetals, but the experimental observation remains challenging. Here, Ni et al. observe a large topological longitudinal photocurrent in CoSi, which is much larger than the photocurrent in any other chiral crystals, indicating quantized CPGE within reach upon doping and increase of the hot-carrier lifetime.